Indigenous knowledge management - multimedia capture of oral history (New lamps for old) - Peter, Woods; Mat Sin, Nazirah; Ab Aziz, Azira (2010)
The history or origins of a village has always been transmitted through oral storytelling by the older generations who have lived in that village for a long time. In order to collect and preserve this tacit knowledge, Perbadanan Perpustakaan Awam Selangor (PPAS) the Selangor State Public Library, in collaboration with Discovery Research Consultant Management Sdn. Bhd and Unit Perancang Ekonomi Negeri Selangor (The Selangor Stae Ecomonic Unit) decided to collect oral histories of villages in Sabak Bernam, which is one of the districts in Selangor, a state in Peninsular Malaysia. With the realization that knowledge is a core resource, they captured and documented all the oral histories (tacit knowledge) into a book (explicit knowledge) called “KOLEKSI CERITA RAKYAT: DAERAH SABAK BERNAM”. Through the oral histories told to them by the older inhabitants, they managed to collect 53 stories of villages in Sabak Bernam. Though the PPAS initiatives were good, the book failed to catch the younger generation’s attention. Now in conjunction with the Faculty of Creative Multimedia, Multimedia University, they have taken one step further by converting the book into animation format.